NEGOSIASI BISNIS DALAM PERSAINGAN GLOBAL - Lasmaya, S. Mia (Majalah Bisnis & IPTEK, 2021)
In face-to- face negotiations, will be tested ingenuity, tenacity and expertise of an employer to prove that he is not just a champion who only dare in his own country but is also able to compete in the international business world. Therefore should the importers and exporters to understand the ins and outs actually business negotiations, especially regarding international business. Keywords: negotiations; businessman